2015
DOI: 10.2220/biomedres.36.135
|View full text |Cite
|
Sign up to set email alerts
|

<b>The effect of repetitive mild hyperthermia on body temperature, the autonomic nervous system, and innate and adaptive </b><b>immunity </b>

Abstract: The effect of repetitive mild hyperthermia on body temperature, the autonomic nervous system, and innate and adaptive immunity was investigated using a new hyperthermia treatment system, nanomist sauna (NMS). Six healthy volunteers participated and the concentration of catecholamines and cortisol, and the frequency and function of leukocytes in the peripheral blood were investigated before and after successive 7 days of hyperthermia treatment (20 min/day, 40°C, 100% relative humidity). After treatment, the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In humans, Tomiyama et al (11) have evaluated the effect of mild hyperthermia treatment on healthy adults, reporting an enhancement of innate and adaptive immunity. Another study focused on the characterization of the response of Dendritic Cells (DCs) to Aspergillus fumigatus at two different temperatures (homeostasis at 37ºC, and fever-like temperature at 40ºC), having found no differences in DC viability or cytokine release, but a higher maturation rate for DCs and a lower phagocytic capacity at 40ºC (31).…”
Section: Effects Of Fever On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, Tomiyama et al (11) have evaluated the effect of mild hyperthermia treatment on healthy adults, reporting an enhancement of innate and adaptive immunity. Another study focused on the characterization of the response of Dendritic Cells (DCs) to Aspergillus fumigatus at two different temperatures (homeostasis at 37ºC, and fever-like temperature at 40ºC), having found no differences in DC viability or cytokine release, but a higher maturation rate for DCs and a lower phagocytic capacity at 40ºC (31).…”
Section: Effects Of Fever On the Immune Systemmentioning
confidence: 99%
“…Some studies have shown the importance of these types of considerations when evaluating hyperthermic incubation conditions compared with the homeostasis temperature of 37°C (10). Therefore this review will focus on fever as an important variable to be considered in infectious diseases research, focusing especially on studies that reported how pyrexia can affect on the one hand the host immune response (11), and on the other hand the pathogen response.…”
Section: Introductionmentioning
confidence: 99%
“…Acute heat stress has been shown to increase the TNF-alpha response of monocytes ( Zellner et al, 2002 ), enhance interleukin-2 induced activity of Natural Killer (NK) cells ( Kappel et al, 1991 ), and cause a 10-fold increase in interferon-γ production by T-lymphocytes ( Downing et al, 1988 ) while regular heat-stress has been shown to reduce adrenaline and cortisol, increase the cytotoxicity of NK cells, and enhance the proliferative response of B cells ( Tomiyama et al, 2015 ). Heat-stress also stimulates the release of Heat Shock Proteins (HSPs), ( Iguchi et al, 2012 ) which play an important role in antigen presentation and cross-presentation, activation of macrophages and lymphocytes, and activation and maturation of dendritic cells ( Tsan & Gao, 2009 ) as well as serving a chaperone function and protecting immune cells and proteins from heat-induced damage ( Singh & Hasday, 2013 ).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The susceptibility window to infections after heavy training is a temporary phenomenon than can last from several hours to days [30], so, another important preventive measure to preserve the body in the susceptibility window, is to adopt physical measures during the recovery phases, for example hyperthermia (saunas) in the cold environments has been shown to be an effective method. Repetitive mild hyperthermia has been proven to be effective in elevating CD56(+) NKT and B and T cells after 7 days of daily exposure at 40 degrees [31,32]. After exercise, cryotherapy has shown to have some effect on immune system recovery [33], lowering peripheral in ammation.…”
Section: Sport and Upper Respiratory Tract Infectionsmentioning
confidence: 99%